Surface and grain boundary segregation in 16MND5 steel. (24th January 2017) - Morvan, Tanguy; Ganster, Patrick; Barnier, Vincent; Wolski, Krzysztof
Abstract : An adequate model of quantification when there are many segregating elements is required for industry and research. Hence, for the first time, surface segregation kinetics on industrial 16MND5 steel was studied by XPS spectroscopy at temperatures ranging from 500 to 600  o C. From measurements that highlight the competitive segregation of P, S, Sn, Sb, As, and Cu impurities at the surface, a quantification model was developed and successfully used to deduce the surface concentrations during segregation kinetics as well as derive the corresponding diffusion coefficients. We observed that phosphorus and sulfur are the first elements covering the surface, then they are supplanted by others' impurities. This result may reflect impurities segregation behavior at the grain boundaries that impacts mechanical behavior of the material. Indeed, to further the research, 16MND5 samples were aged in the same range of temperatures. Then, Auger spectroscopy measurements at grain boundaries were conducted on broken samples exhibiting intergranular cracking. Results show that phosphorus is the only segregating element present at grain boundaries after 2 months of aging. Importantly, it appears that phosphorus grain boundary segregation kinetics is significantly lower than at surface. Copyright © 2017 John Wiley & Sons, Ltd.